COMBINED PERICAPSULAR NERVE GROUP AND OBTURATOR NERVE BLOCKS (PARTHA’S COMBO BLOCK) FOR EMERGENCY REDUCTION OF DISLOCATED PROSTHETIC HIP: A CASE REPORT - KALSAD, ANUSHA; S, PARTHASARATHY (Asian Journal of Pharmaceutical and Clinical Research, 2022)
The perioperative management of hip fractures and dislocation of hips with already fixed hardware are challenging in the elderly because of poor physiological reserve and multiple comorbidities. Previously, general anesthesia and a few regional anesthetic techniques were used to reduce dislocated hip. The pericapsular nerve group block (PENG) was first described in 2018, especially for total hip arthroplasties for a near-complete perioperative analgesia with motor sparing. In this case, a 75-year-old male with a history of hemiarthroplasty 15 days prior presents with a repeat fall and hip injury. We used a combined PENG and obturator nerve (ON) block to treat a dislocated prosthetic hip with a fractured pubic ramus. PENG was given with 20 ml of 0.375% bupivacaine and 6 ml each was administered for the anterior and posterior branches of ON. Following this Partha’s combo block (PENG block+obturator), pain score reduced to 1/10 in around 20 min and closed reduction was done successfully in 4 min. The reduction was successful, painless, and without any major side effects. This is the first such report of reduction of dislocation of prosthetic hip. We surmised that a good pain relief of pubic fracture and the relief of associated adductor spasm targeted by the ON block may be the key to our success.